2020
DOI: 10.1109/access.2020.3013320
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Predictive Model to Predict the Early Mortality Risk in Intensive Care Units on a Highly Imbalanced Dataset

Abstract: Due to the development of biomedical equipment and healthcare level, especially in the Intensive Care Unit (ICU), a considerable amount of data has been collected for analysis. Mortality prediction in the ICUs is considered as one of the most important topics in the healthcare data analysis section. A precise prediction of the mortality risk for patients in ICU could provide us with valuable information about patients' lives and reduce costs at the earliest possible stage. This paper aims to introduce a new hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The authors developed an SVM and SMOTE hybrid strategy (SVM-SMOTE) that included several methods, including a Genetic Algorithm (GA) for feature selection (FS) and Stacking and Boosting (EM) for prediction. SVM-SMOTE was used to tackle imbalanced data problems [65]. Using clustering, weighted scoring, SVM, and EM, Ksieniewicz et al suggested a hybrid method for managing severely imbalanced data categorization in geometric space [66].…”
Section: Ghorbani Et Al Proposed a New Hybrid Model Based On Amentioning
confidence: 99%
See 1 more Smart Citation
“…The authors developed an SVM and SMOTE hybrid strategy (SVM-SMOTE) that included several methods, including a Genetic Algorithm (GA) for feature selection (FS) and Stacking and Boosting (EM) for prediction. SVM-SMOTE was used to tackle imbalanced data problems [65]. Using clustering, weighted scoring, SVM, and EM, Ksieniewicz et al suggested a hybrid method for managing severely imbalanced data categorization in geometric space [66].…”
Section: Ghorbani Et Al Proposed a New Hybrid Model Based On Amentioning
confidence: 99%
“…BPFs [180], MPRM [181] Speech Recognition AL [168] Social Media PCA + DA + CNN [145] Imaging GSVM-BA [182] Spam Detection SMOTE-tBPSO-SVM [183] Malware Detection Boosting + Sampling [184], SMOTE + RF [185] Medical GA + SVM-SMOTE [65] Mortality Prediction Ensemble + SMOTE [71] Sentiment Analysis…”
Section: A Related Study On Himc Data Frameworkmentioning
confidence: 99%
“…Additionally, machine learning is a potential method in improving various functions in the healthcare sector. The application also enhances the diagnostic accuracy for further exploration and remedial procedures and subsequently mitigates hospital readmission, increasing service expenses (59)(60)(61).…”
Section: Prioritisation Predictive Systemmentioning
confidence: 99%
“…Nowadays, massive volumes of data recorded in electronic health records (EHRs) also supported researchers to design models and algorithms for in-hospital mortality prediction which aim at improving the predicting performance and facilitating the clinical decision making. Outperformance of mortality prediction methods based on machine learning models have been shown by many works [6][7][8][9][10][11][12][13]. Some of them show better prediction performance of machine learning models than traditional scoring systems [7,8] and some of them develop various models and machine learning algorithms for mortality prediction [6,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Outperformance of mortality prediction methods based on machine learning models have been shown by many works [6][7][8][9][10][11][12][13]. Some of them show better prediction performance of machine learning models than traditional scoring systems [7,8] and some of them develop various models and machine learning algorithms for mortality prediction [6,[9][10][11][12][13]. Further more, the deep learning models achieve particularly satisfactory performance in ICU mortality prediction tasks due to their strong ability of capturing non-linear patterns hidden in data [14].…”
Section: Introductionmentioning
confidence: 99%